The rise of politically motivated cyber attacks : actors, attacks and cybersecurity - Munk, Tine, 1970- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book outlines the complexity in understanding different forms of cyber-attacks, the actors involved, and their motivations. It explores the key challenges in investigating and prosecuting politically motivated cyber-attacks, the lack of consistency within regulatory frameworks, and the grey zone that this creates, for cybercriminals to operate within. Connecting diverse literatures on cyberwarfare, cyberterrorism and cyber-protests, and categorising the different actors involved - state-sponsored/ supported groups, hacktivists, online protestors - the book compares the means and methods used in attacks, the various attackers, and the current strategies employed by cybersecurity agencies. It examines the current legislative framework and proposes ways in which it could be reconstructed, moving beyond the traditional and fragmented definitions used to manage offline violence. The book is an important contribution to the study of cyber-attacks within the areas of criminology, criminal justice, law and policy. It is compelling reading for all those engaged in cybercrime, cyber-security and digital forensics"--
The growing online threat. The actors -- Cyber attacks, means and methods -- Cybersecurity and strategies -- Cyberwar and warfare: state and state-sponsored attacks -- Cyberterrorism and ransomware: state-supported groups -- Other politically motivated attacks: political activists and hacktivists.
OCLC-licensed vendor bibliographic record.
Keywords: Cyberterrorism; Computer crimes -- Political aspects; Political crimes and offenses; Computer crimes -- Law and legislation; COMPUTERS / Security / General; COMPUTERS / Social Aspects / General; COMPUTERS / Social Aspects / Human-Computer Interaction